ChemInform Abstract: Continuous Flow Synthesis of β‐Amino Acids from α‐Amino Acids via Arndt—Eistert Homologation. Issue 9 (March 2015) - Pinho, Vagner D.; Gutmann, Bernhard; Kappe, C. Oliver
Abstract Two different approaches are developed ‐ the photochemical and silver‐catalyzed ones.